Silicene transistors— A review*Project supported by the National Natural Science Foundation of China (Grant Nos. 11274016, 11474012, and 1207141) and the National Basic Research Program of China (Grant Nos. 2013CB932604 and 2012CB619304). (August 2015) - Quhe, Ru-Ge; Wang, Yang-Yang; Lü, Jing
Abstract Free standing silicene is a two-dimensional silicon monolayer with a buckled honeycomb lattice and a Dirac band structure. Ever since its first successful synthesis in the laboratory, silicene has been considered as an option for post-silicon electronics, as an alternative to graphene and other two-dimensional materials. Despite its theoretical high carrier mobility, the zero band gap characteristic makes pure silicene impossible to use directly as a field effect transistor (FET) operating at room temperature. Here, we first review the theoretical approaches to open a band gap in silicene without diminishing its excellent electronic properties and the corresponding simulations of silicene transistors based on an opened band gap. An all-metallic silicene FET without an opened band gap is also introduced. The two chief obstacles for realization of a silicene transistor are silicene's strong interaction with a metal template and its instability in air. In the final part, we briefly describe a recent experimental advance in fabrication of a proof-of-concept silicene device with Dirac ambipolar charge transport resembling a graphene FET, fabricated via a growth-transfer technique.